The Role of Using Brainstorming Strategy in Increasing The Performance of Students Among The International Exams From School Principals Perspective In Ajloun Directorate - Wahsheh, Dalal Abdallah Altalab (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify The role of using brainstorming strategy in increasing students' performance among the international exams from school principals perspective in Ajloun directorate. To achieve the objectives of the study, the researcher used the descriptive quantitative analytical approach, the sample of study consisted from (95) female and male school principals, and a questionnaire for data collection; it consisted of (23) statements divided to 3 sector (Math, Scince, Reading). The results indicated that the role of using brainstorming strategy in increasing students' performance among the international exams from school principals perspective in Ajloun directorate was High with average (4.01) , and there were no statistical significant differences at (α ≤ 0.05) in the variable of sex, and principal qualification.
Keywords: Brainstorming Strategy; International Exam; School Principals; Ajloun